190k views
4 votes
Step 1 ⇒ x - 3 = 3(x + 3)

Step 2 ⇒ x - 3 = 3x + 9
Step 3 ⇒ x = 3x + 12
Step 4 ⇒ -2x = 12
Step 5 ⇒ x = -6

Identify the property of equality which yields Step 5.

2 Answers

5 votes

Answer:

the answer is property of division

Explanation:

look at step 4 then compare it to step 5 how 12 got divided by

User Evan Anderson
by
4.8k points
5 votes

In step four, you'd divide each side by -2 to isolate x

By dividing both sides by -2, you are using the property of equality and it gets you to the answer in Step 5.

User Enjoli
by
4.6k points